Manajemen Proyek Sistem Informasi Pengaduan Pegawai Di Badan Keuangan Dan Aset Daerah Provinsi Sumatera Utara - Elvan Dito Siregar; Yahfizham Yahfizham (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
This research aims to improve efficiency and effectiveness in handling employee complaints at the Regional Finance and Asset Agency of North Sumatra Province. By developing a complaint management information system based on the waterfall method, this research parses the problem of slow and non-optimal manual processes. The proposed system is expected to support the realization of good governance by accelerating, increasing accuracy, increasing transparency, and increasing accountability in handling complaints. The findings of this research provide insight into the importance of efficient information system implementation in the context of public services in local government.